Концепции космотеории (Сообшение 11) - Суворов, Н.П. (Медична гідрологія та реабілітація, 2009)
Дана публікація є продовженням викладу погляду автора на стратегію розвитку людини. In the present publication conduct the scientifically grounded of harmony as universal philosophical-mathematical law of development of including yourself of the quality and quantity categories.